Supplementing lectures on recursive C programming with an interactive learning environment - Lim, Nathalie Rose T. (Animo Repository, 2006)
Computer programming is one of the foundation courses taken by Computer Science freshmen students of De La Salle University. Fresh from high school where the majority of the students have not been exposed to programming or even algorithm formulation, the students find it difficult to create solutions to programming problems. This paper describes our experience in the development and use of a computer-based learning tool to help students better understand programming concepts. Specifically, this tool focuses on the topic of recursion in the context of C programming. The students are assumed to be knowledgeable in creating and using functions using the C programming language. This software tool is an interactive learning environment (ILE) to supplement lectures on recursive C programming. An ILE for programming aims to assist students hone their problem solving skills through programming, specifically in clarifying student's thoughts about thinking and improve student's thinking habits. This approach requires the student to write a computer program, thus applying the educational philosophy of learning by doing. The developed ILE, thus, provides an editor where the user may program and/or answer programming exercises. Sample C programs and answers to exercises may also be loaded into the editor. The answers to the exercises may be submitted for system evaluation. A system-generated feedback is given to the student to encourage him to try again. In addition, C programs loaded or typed in the editor can be simulated to show how the program executes step by step. The ILE was used by a select group of students. Performance of the control group is compared to that of the experimental group through pre-test and post-test. Results show that (at an average) students who used the ILE scored higher in the posttest than the control group. © 2006 IEEE.